Influence of the Variety and Cooking Method on Glycemic Index of Yam - Kouassi, Nestor Kouakou; Tiahou, Georges Gnomblesson; Fete Abodo, Jacko Rhedoor; Camara-Cisse, Massara; Amani, Georges N`Guessan (Pakistan Journal of Nutrition, 2009)
The aim of the study was to evaluate the impact of variety and cooking method on glycemic index of yams consumed in Cote d’Ivoire. On different occasions, human volunteers consumed 50 g of available carbohydrate in yams varieties cooked either in boiled water or in a conventional oven after 10-12 h overnight fast. The glycemic index values were calculated after measured venous-blood glucose before and after ingestion at 0, 15, 30, 45, 60, 90 and 120 min. The GI results showed that in each variety of yams, the glycemic index does not vary whatever the cooking method. But, considering the yam specie, the glycemic index values varied significantly depending on the variety and cooking method used. The comparison of glycemic index of yams varieties showed differences of clinical importance and could form a basis for dietary advice to diabetic subjects.